Vaccines save lives (Actualizaciones en Sida e Infectología, 2023)
According to the World Health Organization (WHO), vaccines and safe drinking water are the two most important health strategies for disease prevention. Argentina has a national vaccination calendar (NVC) that includes free and compulsory vaccines. It went from being almost exclusively for children to offering vaccines for all stages of life. When we say that the vaccines included in the NVC are free and mandatory, we are referring to a right but also to an obligation, because vaccines not only protect those who receive them but also those around them. Vaccines are solidarity-based. The fact that they are free of charge introduces the concept of equity; anyone who has an indication can receive them. Vaccine-preventable diseases are serious and can lead to severe complications, sequelae and even death. But vaccines are also victims of their own success. Thanks to them, some diseases are controlled and are very infrequent. This leads to a low perception of the risk of disease in the population and in the health team, generating a decrease in vaccination coverage, which could result in the re-emergence of previously-controlled pathologies. It is important to clarify that eliminating a disease is not the same as eradicating it. Eliminating a disease implies that the circulation of the infectious agent that produces it is interrupted. This is achieved if there are good vaccination coverages, i.e. if all the people who should be vaccinated are indeed vaccinated (or at least a large percentage). If vaccination coverage decreases, diseases return. In other words, we must continue vaccinating to sustain the elimination status. In the case of disease eradication, the infectious agent is no longer circulating anywhere on the planet and vaccination is no longer necessary. The classic example of an eradicated disease is human smallpox. Recently, thousands of cases of monkeypox have been reported, produced by a virus of the same family as the one that caused human smallpox, but it is a different disease. When we talk about vaccines, it is always tempting to refer to the myths surrounding this topic, but this is not a good strategy from a communication point of view. When we want to disprove a myth, we can inadvertently install it, and that could lead to serious consequences. It is more effective to provide a positive message without referring to the myth, at least not directly. In Argentina and in the Americas region, the vast majority of people adhere to vaccination programs and have their vaccination schedules completed or, at least, started. There is a very small minority group of people (the so- called “antivaccine”) but very “noisy” in forums and social networks. This group is resistant to scientific evidence, i.e. no matter how many papers or publications we show them, nothing is going to make them change their minds. But we said that the majority of the population adheres to vaccination and, at the other extreme, there is this group of people who, regardless of what we tell them, are not going to get vaccinated. In the middle of these two groups there are people who have genuine doubts regarding vaccines and, in this sense, it is essential that, as health professionals, we can listen to them, with empathy and without judgment, to answer each of these doubts and provide an evidence- based response. It is in this group of people who doubt about all or some of the vaccines where we have to put all the energy, in order to answer their questions and concerns that often lie in the lack of information or false information circulating in the media, social networks and WhatsApp groups. To talk about pro-vaccine and anti-vaccine is a false dichotomy because scientific evidence is one, it is not subjective, it is not a matter of taste or opinion. No one would think of setting up a debate on television discussing the usefulness of drinking water with a graph reading “Drinking water, yes or no: the debate”. However, this has happened more than once in our country. Between 2009 and 2019, there was a 10-point drop in vaccination coverage in our country and in the region of the Americas. Later, the pandemic and the restrictions it demanded caused, among other consequences, an abrupt drop in coverage: for most vaccines, coverage did not reach 80%. This implies a public health problem due to the risk of reintroduction of previously-controlled diseases. The lack of recommendation by health personnel is one of the factors that may affect adequate vaccination coverage in the population and the number of doses administered. For this reason, it is essential that the entire health team work together to initiate or complete  vaccination schedules. It is important to remember that vaccination schedules initiated should be completed, not restarted. The most important thing we can do as health professionals is always to listen and explain, and not to point fingers or judge. If a family that has not vaccinated their children so far comes to the clinic or the vaccination center because they have decided to start, we should welcome them with open arms and tell them that it is never too late.  Sources:1. Argentine Society of Vaccinology and Epidemiology (SAVE) 2. Argentine Society of Infectious Diseases (SADI) 3. PAHO4. Ministry of Health of Argentina
Keywords: vaccines; health strategy; national vaccination calendar